The impact of county-level fees & fines as exploitative revenue generation on US birth outcomes 2011–2015. (March 2023) - Davis, Brigette A.; Arcaya, Mariana C.; Williams, David R.; Krieger, Nancy
Abstract: Fees and fines collected through courts and law enforcement can comprise a considerable proportion of revenue for local governments. Law enforcement, as agents of revenue generation, change policing behavior to increase revenue, at times targeting Black and brown neighborhoods to bolster municipal budgets. This structural racism in revenue generation has not yet been assessed as an exposure for adverse health. Using the 2012 Census of Governments, and 2011–2015 vital statistics from the National Center of Health Statistics, we examine the relationship between countyaverage fees and fines as a percent of total own-source revenue and county-level characteristics, and risk of preterm birth and low birthweight across the United States. Mothers residing in counties with the greatest reliance on fees and fines had 1.08 (95% CI: 1.03–1.12) times the odds of preterm birth and 1.07 (95% CI: 1.02–1.11) times the odds of low birthweight than mothers residing in counties with the least reliance on fees and fines, controlling for individual- and county-level covariates. The addition of countylevel racial composition, and the Index of Concentration at the Extremes (ICE), reduced these associations yet remained statistically significant. Future studies should continue to examine how racist, exploitative revenue generation through police and court activities influences the health of residents. Highlights: Fees & fines collected through law enforcement and court activities can be used to bolster municipal budgets' revenue. Fees & fines revenue is associated with racial composition and segregation across U.S. Counties. Adverse birth outcomes are greatest in places most reliant on fees & fines revenue.